2020
DOI: 10.1002/2211-5463.12874
|View full text |Cite
|
Sign up to set email alerts
|

Copine A regulates the size and exocytosis of contractile vacuoles and postlysosomes in Dictyostelium

Abstract: Copines are a family of cytosolic proteins that associate with membranes in a calcium‐dependent manner and are found in many eukaryotic organisms. Dictyostelium discoideum has six copine genes (cpnA‐cpnF), and cells lacking cpnA(cpnA−) have defects in cytokinesis, chemotaxis, adhesion, and development. CpnA has also been shown to associate with the plasma membrane, contractile vacuoles (CV), and organelles of the endolysosomal pathway. Here, we use cpnA− cells to investigate the role of CpnA in CV function and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Actin filament dynamics are necessary for the phagocytic engulfment of particles and are important in cell adhesion [ 23 ]. We previously showed that CpnA is able to interact with actin filaments in a calcium-dependent manner and may play a role in actin depolymerization at the surface of membranes [ 13 , 17 ]. To further understand CpnA’s role in adhesion, we used the actin depolymerizing drug, Latrunculin A (LatA) to both inhibit phagocytosis [ 24 ] and to see if actin filaments play a role in the increased adhesion observed in cpnA - cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Actin filament dynamics are necessary for the phagocytic engulfment of particles and are important in cell adhesion [ 23 ]. We previously showed that CpnA is able to interact with actin filaments in a calcium-dependent manner and may play a role in actin depolymerization at the surface of membranes [ 13 , 17 ]. To further understand CpnA’s role in adhesion, we used the actin depolymerizing drug, Latrunculin A (LatA) to both inhibit phagocytosis [ 24 ] and to see if actin filaments play a role in the increased adhesion observed in cpnA - cells.…”
Section: Resultsmentioning
confidence: 99%
“…Altered membrane lipid composition and/or calcium concentrations in cpnA - cells may also contribute to the increased postlysosome exocytosis phenotype we previously reported [ 17 ]. Other studies have reported a link between PS exposure and membrane trafficking.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In round worm C. elegans, Copine controls synaptic expression of nicotinic acetylcholine receptors [ 4 ] and TRP channel GON-2 that stimulates gonadal cell division [ 5 ] and is required for myofilament stability [ 6 ]. In protist, social amoeba Dictiostellium, Copine A is important for cell differentiation, cytokinesis, contractile vacuole function, phospholipid distribution, and slug formation [ 7 , 8 , 9 , 10 , 11 ]. In Copine A mutants, slug formation deficits could be rescued by introducing a small number of wild-type cells into the amoeba population suggesting that Copine regulates the secretion of unknown factors essential for slug formation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%